Difference between revisions of "Truth table proofs"

From Computer Science
Jump to: navigation, search
(Disproof of a logical fallacy)
Line 35: Line 35:
  
 
==Disproof of a logical fallacy==
 
==Disproof of a logical fallacy==
Truth tables can also be used to disprove a logical fallacy. For example, one fallacy is to assume the converse of an implication holds.  If you know that (A → B) is true, and you know that B is true, the fallacy would be to then conclude that A must also be true.  Note that the statement - "if an animal is a mammal then it is also a vertebrate" - is true. If we have an animal that is a vertebrate (for example, a dog), it would be a fallacy to now conclude that the animal must also be a mammal.
+
Truth tables can also be used to disprove a logical fallacy. For example, [https://en.wikipedia.org/wiki/Affirming_the_consequent one fallacy] is to assume the converse of an implication holds.  If you know that (A → B) is true, and you know that B is true, the fallacy would be to then conclude that A must also be true.  Note that the statement - "if an animal is a mammal then it is also a vertebrate" - is true. If we have an animal that is a vertebrate (for example, a dog), it would be a fallacy to now conclude that the animal must also be a mammal.
 +
 
 +
We will show that this is a logical fallacy - regardless of the statements A and B, just because we know A → B is true, we should not in general assume the converse is also true.  First we remind you that (A → B) is equivalent to ¬ A ∨ B.  What we want to look at is the claim: ((A → B) ∧ B) → A. If this expression is always true, then we could rely on the converse to always be used.  Let us first simplify the expression.  It is equivalent to ((¬ A ∨ B) ∧ B) → A. This is equivalent to ¬ ((¬ A ∨ B) ∧ B) ∨ A. We can keep this formula in mind as we evaluate it's truth value for each possible value of A and B.
  
 
Consider this truth table.
 
Consider this truth table.
 
{| class="wikitable"
 
{| class="wikitable"
 
|-  
 
|-  
! A !! B !! A → B (which is equivalent to ¬ A ∨ B)
+
! A !! B !! A → B !! ((A → B) ∧ B) → A
 
|-
 
|-
| false || false || true
+
| false || false || true || true
 
|-
 
|-
| false || true || true
+
| false || true || true || false
 
|-
 
|-
| true || false || false
+
| true || false || false || true
|-
+
|-  
| true || true || true
+
| true || true || true || true
 
|}
 
|}
In the  
+
In the second row, we see that the last column is false. This is where we should expect to see a problem - the place where B is true, but we should not be able to conclude that A must also be true. We have shown that we cannot always apply the converse.
 
 
  
 
=Assignment=
 
=Assignment=

Revision as of 15:20, 29 August 2022

Truth tables are used to show all possible values that a given logical expression might take.

Examples

Definition of AND

The following gives the definition of the logical AND operation.

A B A ∧ B
false false false
false true false
true false false
true true true

Proof of one of De Morgan's laws

A truth table can also be used to prove a logical identity. The following proves De Morgan's law that ¬ (A ∧ B) is equivalent to (¬ A) ∨ (¬ B). Notice that the truth values for these (the last two columns in the table) are always the same.

A B A ∧ B ¬ (A ∧ B) (¬ A) ∨ (¬ B)
false false false true true
false true false true true
true false false true true
true true true false false

Disproof of a logical fallacy

Truth tables can also be used to disprove a logical fallacy. For example, one fallacy is to assume the converse of an implication holds. If you know that (A → B) is true, and you know that B is true, the fallacy would be to then conclude that A must also be true. Note that the statement - "if an animal is a mammal then it is also a vertebrate" - is true. If we have an animal that is a vertebrate (for example, a dog), it would be a fallacy to now conclude that the animal must also be a mammal.

We will show that this is a logical fallacy - regardless of the statements A and B, just because we know A → B is true, we should not in general assume the converse is also true. First we remind you that (A → B) is equivalent to ¬ A ∨ B. What we want to look at is the claim: ((A → B) ∧ B) → A. If this expression is always true, then we could rely on the converse to always be used. Let us first simplify the expression. It is equivalent to ((¬ A ∨ B) ∧ B) → A. This is equivalent to ¬ ((¬ A ∨ B) ∧ B) ∨ A. We can keep this formula in mind as we evaluate it's truth value for each possible value of A and B.

Consider this truth table.

A B A → B ((A → B) ∧ B) → A
false false true true
false true true false
true false false true
true true true true

In the second row, we see that the last column is false. This is where we should expect to see a problem - the place where B is true, but we should not be able to conclude that A must also be true. We have shown that we cannot always apply the converse.

Assignment